A synergistic pedagogical model: Integrating teacher role modeling and guidance to foster spiritual intelligence - Ipih Hidawati; Jamali Jamali; Didin Nurul Rosidin; Widodo Winarso; Siti Fatimah; Iwan Iwan (Journal of Educational Management and Instruction (JEMIN), 2026)
Spiritual intelligence has become a crucial dimension of holistic education, yet it remains underemphasized in many educational practices that prioritize cognitive achievement over spiritual development, particularly amid contemporary adolescent challenges. This study aims to examine how teachers’ role modeling and guidance operate, both independently and synergistically, in shaping students’ spiritual intelligence within a pesantren-based junior high school. Employing a qualitative case study design, the study involved twelve participants, comprising teachers, students, school management personnel, and a pesantren administrator. Data were collected through non-participant observation, in-depth semi-structured interviews, and document analysis, and analyzed using thematic analysis involving coding, categorization, and interpretation. The findings reveal that teachers’ role modeling functions as a consistent embodiment of spiritual values, while guidance operates as a structured and reflective mentoring process that supports students’ internalization of those values. Importantly, the integration of role modeling and guidance creates a synergistic pedagogical approach that promotes deeper spiritual transformation, including self-awareness, moral responsibility, and emotional regulation. This study concludes that a relational and integrative model of spiritual education is more effective than isolated practices and offers both theoretical and practical contributions to strengthening character education in Islamic educational contexts.